Tren Pemikiran Tafsir al-Qur'an di Indonesia: Antara Perkembangan dan Pergeseran - Muhammad Alwi HS dan Teti Fatimah, Alwi (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
Since al-Qur'an is in written form (read: Manuscripts), since then the Qur'an has an open meaning. Anyone can understand it, interpret, and practice the contents based on their understanding. In Indonesia alone, the interpretation of the Qur'an continues to experience significant developments, until now the study of the interpretation of the Qur'an continues. This paper is going to explain the trends in the interpretation of the Qur'an in Indonesia. Through this paper, it will be seen how far Indonesian scholars 'wrestle' with the interpretation of the Qur'an. How is the development of interpretive thinking from classical, modern and contemporary times. Does the changing times bring Indonesian scholars more dominantly to the development of thought or is it only to the shift of thought from an Eastern to the Western style of understanding. As well as what are the expected implications of interpretive thinking on the needs of the Indonesian context.